Sister’s Cafe / Amanda Diasip - Amanda, Diasip (2020)
AD 'S Sister's Sendirian Berhad provides customer-friendly bakery goods and services, including the selection of cake, pastry, bread and brownies that brings maximum customer satisfaction. Most of our customers are medium and upper-class customers who want to purchase products with an extremely affordable price product. We also recruit successful staff, since our service is distributed to the customer's house. Sister's Café provides a range of pastries that provide health-related foods, low sugar, low calories and Halal certificates. Across Sabah and Sarawak, particularly the AD’s Sister’s Sdn. Bhd., the company has seen a year-over-year acceleration in growth. Kota Kinabalu is a region where many couples marry from various cultures and races, but with specific types and tastes the market for cakes grows through the year. While there are four companies like us in Kota Kinabalu at the moment, only this business has a unique delivery services and café. AD’s Sister’s Sdn. Bhd. the marketing strategy consists of highlighting the quality and price of our products and services. We sell the inexpensive quality, since many citizens have very small wage and poor families in Kota Kinabalu. Therefore, we establish a marketing policy that allows our shop especially poor people desirable to visit. The management of AD’s Sister’s Sdn. Bhd. Amanda Diasip, Aileen Diasip, Anastasia Diasip, Abigail Diasip and Desley Calvin represent 5 lead staff. Our employees have vast experience in banking, market, distribution, administration while at the Hotel Sutera Harbour, Aileen is the only employee with experience employed in the bakery market. Because of separate roles and partners' portfolio, five couples will carry on job obligations together. We already have service and product investments, and continue to develop our business actively through newspaper, advertising and signboard. The precious bakery and cake which is the Sdn of AD 's Daughter. Bhd: Bhd. Are sure to draw buyers throughout the Kota Kinabalu and Ranau region.